EFFECTIVE COMMUNICATION IN THE PROMOTION OF HISTORICAL TOURISM IN BENGKULU PROVINCE ON KAKAOTALK CHAT FEATURE - Elena Dwi Febiola; Vethy Octaviani; Yanto Yanto (Universitas Dehasen Bengkulu, 2023)
Research on effective communication in the promotion of historical tourism in Bengkulu Province on the Kakaotalk chat feature, aims to find out how effective communication is carried out by the Tourism Office to prospective South Korean tourists using the Kakaotalk application, the type of research method used is descriptive qualitative method, in finding data researchers use interviews, documentation and data analysis methods. In view of the theory used, namely, the effective communication process by Cutlip and Allen, shows that the first 7 factors are credibility, where the achievements to the form of cooperation built by the Bengkulu Province Tourism Office build strong credibility to attract South Korean tourists, secondly there is a context in this promotion which also explains the conditions or good times for tourists to come to Bengkulu and some of the things they can see in Bengkulu, thirdly this content is also one of the strong factors where the promotion uses several pieces of history to tell stories that make South Korean tourists interested and communicate with the promotion. fourthly clarity (clear message), The fourth is clarity (a clear message), with this translator it really helps the promotion with the tourists to convey the message well, the fifth is the continuity of communication that lasts until now shows that the message is conveyed well and effectively, the sixth is media, using Kakaotalk this really helps good communication and makes better service to South Korean tourists, and the last is understanding, both parties can be said to have effective communication with the same understanding or the message conveyed and received has the same meaning. From these factors contained in the theory after being researched and observed, the results are fulfilled or answered and it can be concluded that communication in the promotion of historical tourism on the kakaotalk chat feature carried out by the Bengkulu Provincial Tourism Office with South Korean tourists has been carried out effectively.